Egyptian Students’ Disinterest in Overseas Academic Mobility: A Behavioral Approach Based on the Capability-Opportunity-Motivation Model - Syed Zwick, Hélène (Journal of International Students, 2021)
This study uses the capability-opportunity-motivation behavior framework as a theoretical basis and partial least squares structural equation modeling as an empirical research method to identify factors that influence the interest in studying abroad. We rely on primary microdata collected through a self-administered questionnaire among Egyptian students and apply a structural equation model to estimate the different relationships. Our analysis yielded interesting results: (a) 58% of our respondents were somehow interested in studying abroad; (b) physical capability, physical opportunity, and automatic motivation were the main predictors of interest in overseas academic mobility; and (c) a three-pillar policy program based on guidelines, communication and marketing, and regulation could be implemented to promote the interest of young Egyptians in studying abroad.